2022
DOI: 10.1002/ece3.8788
|View full text |Cite
|
Sign up to set email alerts
|

Exosymbiotic microbes within fermented pollen provisions are as important for the development of solitary bees as the pollen itself

Abstract: Developing bees derive significant benefits from the microbes present within their guts and fermenting pollen provisions. External microbial symbionts (exosymbionts) associated with larval diets may be particularly important for solitary bees that suffer reduced fitness when denied microbe‐colonized pollen. To investigate whether this phenomenon is generalizable across foraging strategy, we examined the effects of exosymbiont presence/absence across two solitary bee species, a pollen special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 78 publications
0
6
1
Order By: Relevance
“…Although our sterilization method eliminated Arsenophonus and other bacteria from microbe-deficient pollen, larvae reared on sterile provisions had comparable survivorship to bees consuming microbe-rich diets. These results contradict previous research strongly suggesting that larval survivorship depends on the presence of microbes in larval food [12][13][14]. Preliminary data from a recent in vitro study, however, also indicates that provision microbes can have adverse consequences for solitary bee fitness: the addition of Apilactobacillus micheneri (previously Lactobacillus) in the diet of megachilid larvae increased mortality [79], an unexpected result given the frequent detection in solitary bees [66,80,81] and known functions of lactobacilli in eusocial bees (e.g., preventing the spoilage of stored pollen and defense against pathogens) [82,83].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Although our sterilization method eliminated Arsenophonus and other bacteria from microbe-deficient pollen, larvae reared on sterile provisions had comparable survivorship to bees consuming microbe-rich diets. These results contradict previous research strongly suggesting that larval survivorship depends on the presence of microbes in larval food [12][13][14]. Preliminary data from a recent in vitro study, however, also indicates that provision microbes can have adverse consequences for solitary bee fitness: the addition of Apilactobacillus micheneri (previously Lactobacillus) in the diet of megachilid larvae increased mortality [79], an unexpected result given the frequent detection in solitary bees [66,80,81] and known functions of lactobacilli in eusocial bees (e.g., preventing the spoilage of stored pollen and defense against pathogens) [82,83].…”
Section: Discussioncontrasting
confidence: 99%
“…We also found contradictory evidence regarding the importance of the provision microbiota for larval health: immature bees reared on pollen without microbes weighed more than those feeding on microbe-rich provisions. Past studies found that larvae acquire fatty and amino acids from microbial prey within provisions, resulting in heavier bees than those reared on sterile pollen [12][13][14]. These opposing results may be explained by differences in pollen sterilization methods: in choice assays, EO exposure does not affect the palatability of pollen to bumblebees [28], but it is unknown whether soaking provisions in ethanol [12][13][14] affects pollen consumption in solitary bees, perhaps leading to differences in biomass, fat content, and trophic positions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Removing these symbionts can lead to dysbiosis, the lack of beneficial relationships between microbes and their host (Belizário & Faintuch, 2018; Ye et al, 2021). With their absence potentially resulting in declines in growth rate, survivorship, and fitness (Dharampal et al, 2019, 2020, 2022), fostering beneficial microbial communities is one method to support bee health.…”
Section: Introductionmentioning
confidence: 99%